Susceptibility to metazoan parasite infection in amphimictic diploid and induced triploid tench (Tinca tinca L., 1758): the role of parasites in fish aquaculture - Šimková, Andrea; Dávidová, Martina; Hyršl, Pavel; Janáč, Michal; Flajšhans, Martin; Ondračková, Markéta (Frontiers in Veterinary Science, 2025)
IntroductionArtificial induction of polyploidy in fishes is a widely used method in commercial aquaculture due to its economic potential and its association with changes in cell morphology and physiology that can significantly affect individual fitness. Using tench (Tinca tinca, Cyprinidae), a fish species extensively farmed in European aquaculture, we investigated differences in parasite susceptibility between triploid and diploid fish and analyzed the potential effect of metazoan parasite infection on fish condition, physiology, and health status.MethodsAmphimictic diploid and induced triploid specimens collected from a breeding pond were examined during four sampling events over the course of one year, focusing on the presence of metazoan parasites and selected fish condition, physiological, and immune parameters.ResultsDiploids generally exhibited a higher overall parasite load than triploids throughout the year; however, this difference was statistically significant only in summer, coinciding with the extremely high abundance of the tench-specific Asymphylodora tincae. Host ploidy appeared to influence susceptibility or resistance to particular parasite species. While amphimictic diploid tench showed higher susceptibility to adult trematode A. tincae, triploid tench were more parasitized by the larval cestode Valipora campylancristrota. No difference in abundance of monogenean Gyrodactylus tincae was observed between amphimictic diploid and induced triploid specimens. Other parasites were relatively rare in both groups. Although no clear association between parasite infection and the measured physiological or immune parameters was found, significant negative correlations were more frequently observed in diploid fish than in triploids.DiscussionThe differences in parasite infection between triploid and diploid tench and the associations between parasite load and condition- and health-related traits may be explained by (1) presumed higher heterozygosity in triploids, (2) physiological differences related to cell size and number of cells in key organs and tissues, (3) variation in feeding performance, and (4) host–parasite coevolutionary interactions.